Assessment of nailfold capillaries with a handheld dermatoscope may discriminate the extent of organ involvement in patients with systemic sclerosis. Issue 2 (February 2016) - Arana-Ruiz, Juan; Silveira, Luis; Castillo-Martínez, Diana; Amezcua-Guerra, Luis
Abstract To investigate whether nailfold capillaroscopy (NFC) patterns assessed through an in-office handheld dermatoscope may reflect the extent of disease severity in systemic sclerosis (SSc). NFC patterns were evaluated with a non-contact, polarized light dermatoscope in 40 consecutive patients with SSc and graded in sequence as 0 = normal, 1 = early, 2 = active, or 3 = late patterns. Disease severity was measured according to a modified Medsger severity scale (MSS). For comparisons, patients were grouped in tertiles according to disease severity, and a numerical correlation between the NFC patterns and the composite MSS score was assessed. Twenty patients had normal or early NFC patterns, most of them (17 individuals, 85 %) having low to moderate disease severity. In contrast, 18 out of 20 (90 %) patients with active or late NFC patterns had moderate to high disease severity. Accordingly, patients with normal/early NFC patterns had a median MSS score of 4 (interquartile range (IQR), 3–5) as compared with 7 (4–8;P = 0.02) in those with active/late patterns. A Spearman's rho coefficient of 0.45 (95 % CI, 0.15–0.67;P = 0.003) was found between the graded scale of NFC patterns and the composite MSS score. A handheld dermatoscope is useful to visualize the NFC patterns in SSc patients, and it is efficient enough to reflect the extent of disease severity.